Super-Enhancer-Associated Long Non-Coding RNA LINC01485 Promotes Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells by Regulating MiR-619-5p/RUNX2 Axis - Gu, Wenli; Jiang, Xiao; Wang, Wei; Mujagond, Prabhakar; Liu, Jingpeng; Mai, Zhaoyi; Tang, Hai; li, Simin; Xiao, Hui; Zhao, Jianjiang (Frontiers in Endocrinology, 2022)
Objective: To investigate the mechanisms of super-enhancer-associated LINC01485/miR-619-5p/RUNX2 signaling axis involvement in osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs). Methods: Osteogenic differentiation of hBMSCs was induced in vitro. The expression levels of LINC01485 and miR-619-5p during osteogenesis were measured using quantitative real-time polymerase chain reaction (qRT-PCR). Osteogenic differentiation was examined by qRT-PCR, western blot, alkaline phosphatase (ALP) staining, ALP activity measurement, and Alizarin Red S (ARS) staining assays. Thereafter, the effects of LINC01485 and miR-619-5p on osteogenic differentiation of hBMSCs were evaluated by performing loss- and gain-of-function experiments. Subsequently, a fluorescence in situ hybridization (FISH) assay was employed to determine the cellular localization of LINC01485., Bioinformatics analysis, RNA antisense purification (RAP) assay, dual-luciferase reporter assays were conducted to analyze the interactions of LINC01485, miR-619-5p, and RUNX2. Rescue experiments were performed to further delineate the role of the competitive endogenous RNA (ceRNA) signaling axis consisting of LINC01485/miR-619-5p/RUNX2 in osteogenic differentiation of hBMSCs. Results: The expression of LINC01485 was up-regulated during osteogenic differentiation of hBMSCs. The overexpression of LINC01485 promoted osteogenic differentiation of hBMSCs by up-regulating the expression of osteogenesis-related genes (e.g., runt-related transcription factor 2 (RUNX2), osterix (OSX), collagen type 1 alpha 1 (COL1A1), osteocalcin (OCN), and osteopontin (OPN)), and increasing the activity of ALP. ALP staining and ARS staining were also found increased upon overexpression of LINC01485. The opposing results were obtained upon LINC01485 interference in hBMSCs. miR-619-5p was found to inhibit osteogenic differentiation. FISH assay displayed that LINC01485 was mainly localized in the cytoplasm. RAP assay results showed that LINC01485 bound to miR-619-5p, and dual-luciferase reporter assay verified that LINC01485 bound to miR-619-5p, while miR-619-5p and RUNX2 bound to each other. Rescue experiments illustrated that LINC01485 could promote osteogenesis by increasing RUNX2 expression by sponging miR-619-5p. Conclusion: LINC01485 could influence RUNX2 expression by acting as a ceRNA of miR-619-5p, thereby promoting osteogenic differentiation of hBMSCs. The LINC01485/miR-619-5p/RUNX2 axis might comprise a novel target in the bone tissue engineering field. Keywords: LINC01485; miR-619-5p; RUNX2; super-enhancers; bone marrow mesenchymal stem cells; osteogenesis; osteogenic differentiation.